The Consequences of Aging On the Response to Injury and Critical Illness. Issue 2 (August 2020) - Joseph, Bellal; Scalea, Thomas
Abstract : ABSTRACT: Changing demographic trends have led to an increase in the overall geriatric trauma patient volume. Furthermore, the intersection of aging and injury can be problematic because geriatric patients have multiple comorbidities, geriatric-specific syndromes, and reduced physiological reserve. Despite mounting evidence that frail geriatric patients have inferior outcomes following trauma, very few studies have examined the effect of aging on the biological response to injury. In the present article, we review the current literature and explore the pathophysiological rationale underlying observed data, available evidence, and future directions on this topic.